MOOD DISORDER OF MAGGIE AS THE MAIN CHARACTER IN HENRY HOBSON’S FILM MAGGIE: A PSYCHOLOGICAL APPROACH - Nanga, Vinsensius; Wanggai, Febe F I; Doi, Maksimilianus (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2022)
Analyzing mood disorder in Henry Hobson’s film Maggie was actually chosen by the writer since there was less attention and misconception in our broad society. What people know about this psychology problem is very limited. People assumed that it is very common and it is not quite important to take a deep understanding in this problem. Furthermore, this study aimed at finding out the types of mood disorder by recognizing every symptoms of the disorder found in Maggie film. The method of the study was descriptive qualitative that explored about the types of mood disorder itself and recognized each type according to the symptoms shown by one of the characters in the film by using two steps. The first was watching the film closely, and the second was finding out all the quotations in some dialogues belonging to the problem. Through the data presented in findings and discussion section, the mood disorder as well as is experienced by Maggie as the main character in the film. There are two general types of mood disorder suffered by Maggie. They are depressive disorder and bipolar disorder in which they were also included some types such as major depressive disorder, chronic depressive disorder, and bipolar disorder I